Pangolin-inspired stretchable, microwave-invisible metascale - Wang, Changxian (2022)
Microwave-invisible devices are emerging as a valuable technology in various applications, including soft robotics, shape-morphing structures, and textural camouflages, especially in electronic countermeasures. Unfortunately, conventional microwave-absorbing metastructures and bulk absorbers are stretching confined, limiting their application in deformable or special-shaped targets. To overcome such limitations, a conceptually novel soft-rigid-connection strategy, inspired by the pangolin, is proposed. Pangolin-inspired metascale (PIMS), which is a kind of stretchable metamaterial consisting of an electromagnetic dissipative scale (EMD-scale) and elastomer, is rationally designed. Such a device exhibits robust microwave-absorbing capacity under the interference of 50% stretching. Besides, profiting from the covering effect and size-confined effect of EMD-scale, the out-of-plane indentation failure force of PIMS is at least 5 times larger than conventional device. As a proof of concept, the proposed device is conformally pasted on nondevelopable surfaces. For a spherical dome surface, the maximum radar cross-section (RCS) reduction of PIMS is 6.3 dB larger than that of a conventional device, while for a saddle surface, the bandwidth of 10 dB RCS reduction exhibits an increase of 83%. In short, this work provides a conceptually novel platform to develop stretchable, nondevelopable surface conformable functional devices.